The influence of lifestyle and consumption values on the second-hand clothing buying behaviour of consumers in South Africa - Taljaard-Swart, Hanri (University of Pretoria, 2024)
Dissertation (MConsumerScience (Clothing Management))--University of Pretoria, 2024.